STUDI DESAIN STIMULASI INJEKSI GAS NITROGEN PADA SUMUR GEOTHERMAL DOMINASI AIR DENGAN VALIDASI DATA DI LAPANGAN - Kamila, Zahratul
Gothermal wells in liquid dominated system usually cannot flow naturally so it needs to be stimulated to initiate flow from wellbore to surface. It is different from vapour dominated system where wells can flow and produce fluids without help of stimulating technique. There are a lot of stimulation methods which can be conducted to discharge the wells such as air compression, well-to-well stimulation and nitrogen gas injection. In particular, this study will focus on nitrogen injection stimulation method. Nitrogen gas injection method in general is to inject nitrogen gas with its flow rate to the well bore therefore it can reduce the hydrostatic pressure around the main permeable zone so that it reach its boiling condition. This study will select Harrison-Fresston correlation and mechanistic model by Caetano to calculate nitrogen gas flow rate and volume needed to remove the weight of liquid column in the wellbore. The computation results will be compared with the actual field data. The assumptions are: two phase flow mechanism in annulus, no diameter change in the casing, slug flow pattern, and gas bubbles flow in stagnant column of liquid. From this study, we can refer that gas fow rate from computation result compare to field data can have bigger deviation value at deep water column condition. On the other hand, at shallow water depth or almost near to surface, the results of study will show the lower values of deviation or the error. At the end, the selected correlation can be used to predict the actual volume of nitrogen, mainly if the submergence ratio is bigger than or equal to 0.55 where the results of computation will close to field data